To study surgical outcome of various surgical procedures of lateral release in valgus knee in total knee arthroplasty - Patel, Ankit; Shah, Hiren; Shah, Aalok; Gajjar, Sharvil Hetavbhai; Shah, Ripple; Shah, Suril (International Journal of Research in Orthopaedics, 2017)
Background: Fixed valgus deformity presents a major challenge in total knee arthroplasty (TKA), especially in moderate or severe cases. In knee arthritis, fixed-varus deformity (50 to 55%) is three times more frequent than fixed-valgus deformity (10 to 15%). Valgus deformity occurs more commonly in rheumatoid arthritis and also in osteoarthritis with hypoplasia of the lateral femoral condyle. Valgus deformity is often associated with flexion or external rotation contracture of the knee. In this study we aim to study the surgical outcome of total knee replacement in valgus deformity via standard medial parapatellar approach using various techniques like Pie –Crusting release of lateral structures or combined technique of pie crusting and standard release of lateral structures. Aim: To evaluate surgical outcome of various surgical techniques via standard medial parapatellar approach in fixed valgus deformity in Total Knee Arthroplasty. Methods: The present study involved both male and female patients with osteoarthritis of knee with valgus deformity. In present series, 26 consecutive patients of osteoarthritis with valgus deformity operated with total knee replacement were included. Previously operated cases of high tibial osteotomy and patients having contraindication for TKA were excluded from the study. Results: Valgus angle in this study was between 13 to 27 degree with average 17.84 degree. These results were comparable to many such similar studies. In our study, post operatively, knee society score was average 87.69 and function knee score was 82.5. Mean range of motion was 105 degree. In our study, mean tibiofemoral alignment improved from 17.84 valgus to 4.7 valgus. Conclusions: Knee society score is excellent with both techniques and there is no difference in both techniques Iliotibial band and posterolateral capsule are most common structures that require release. Initial ligament balancing should be done with pie crusting and then sequential lateral release if require.